2000
DOI: 10.1021/jm000006z
|View full text |Cite
|
Sign up to set email alerts
|

Cation Substitution in Cationic Phosphonolipids:  A New Concept To Improve Transfection Activity and Decrease Cellular Toxicity

Abstract: Cationic lipids have been shown to be an interesting alternative to viral vector-mediated gene delivery into in vitro and in vivo model applications. Prior studies have demonstrated that even minor structural modifications of the lipid hydrophobic domain or of the lipid polar domain result in significant changes in gene delivery efficiency. Previously, we developed a novel class of cationic lipids called cationic phosphonolipids and described the ability of these vectors to transfer DNA into different cell lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
97
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 115 publications
(104 citation statements)
references
References 37 publications
5
97
0
1
Order By: Relevance
“…Preparation and Characterization of Cationic Liposomes Cationic lipids were often mixed with a neutral colipid dioleoylphosphatidylethanolamine (DOPE) to formulate into cationic liposomes. [42][43][44][45][46][47] The results of the particle size, size distribution and zeta potential of the cationic liposomes were shown in Table 1. The cationic formulation of two cationic lipids at lipid/DOPE ratio of 1 : 1 exhibited rather small hydrodynamic diameters 78.2 nm for T-C12-AH and 83.7 nm for T-C16-AH.…”
Section: Synthesis Of the Cationic Lipids T-c12-ah And T-c16-ah The Cmentioning
confidence: 99%
“…Preparation and Characterization of Cationic Liposomes Cationic lipids were often mixed with a neutral colipid dioleoylphosphatidylethanolamine (DOPE) to formulate into cationic liposomes. [42][43][44][45][46][47] The results of the particle size, size distribution and zeta potential of the cationic liposomes were shown in Table 1. The cationic formulation of two cationic lipids at lipid/DOPE ratio of 1 : 1 exhibited rather small hydrodynamic diameters 78.2 nm for T-C12-AH and 83.7 nm for T-C16-AH.…”
Section: Synthesis Of the Cationic Lipids T-c12-ah And T-c16-ah The Cmentioning
confidence: 99%
“…Experiments were done with the third-generation phosphonolipid transfection reagent KLN143, containing an ammonium polar head. It was used and formulated as previously described for the second generation of cationic phosphonolipids (29,30). Briefly, cationic lipids were dissolved in chloroform in a glass vial.…”
Section: In Vivo Experimentsmentioning
confidence: 99%
“…Ever since Felgner et al 3 reported their pioneering development of cationic lipid-mediated gene delivery protocol in 1987, many reports aimed at developing more efficient cationic transfection lipids have appeared in the literature. [4][5][6][7][8][9][10] Recently, we have also developed efficient nonglycerol-based cationic transfection lipids. [11][12][13][14][15] In sharp contrast, details of cationic lipid-mediated transfection pathways still remain elusive.…”
Section: Introductionmentioning
confidence: 99%